Myriad of magnetic resonance imaging findings in human immune deficiency virus positive patients with central nervous system manifestations - Kathpalia, Sudhanshu; Sachdev, Namrita; ., Priyanka; Nanda, Civilee (International Journal of Research in Medical Sciences, 2022)
Human immuno-deficiency virus (HIV) is a neurotropic virus that affects the central nervous system (CNS) early in the course of illness. Neurological complications are seen in about 60% of the patients and were the major presenting complaints in 20% patients in the pre-highly active anti-retroviral therapy (HAART) era. Imaging especially magnetic resonance imaging (MRI) is thus helpful in shedding light on the causative factor of neurological symptoms in acquired immunodeficiency syndrome (AIDS) patients. It can be used as an adjunct to clinical features and serological/cerebrospinal fluid (CSF) findings to diagnose CNS abnormalities with greater confidence and modify therapeutic strategy accordingly. We conducted a cross-sectional observational study with 12 HIV positive patients for a period of 12 months. MRI evaluation was done using conventional brain sequences. HIV encephalopathy was diagnosed on imaging in 8 patients, polymorphic light eruption (PMLE) in 2 patients, CNS toxoplasmosis in 1 patient and CNS lymphoma in one patient. The clinical details and imaging features of the various manifestations are described. Though there might be a certain degree of overlap in the imaging findings, some imaging findings provide important diagnostic clues for specific diseases, especially on MRI.